Materials Science and Technology of Additive Manufacturing Selected, peer-reviewed papers from the conference Materials Science and Technology of Additive Manufacturing 2019 (MSTAM), December 10-11, 2019, Bremen, Germany - Ploshikhin, Vasily; Jürgens, Jan-Patrick; Siewert, Marvin (Trans Tech Publications, Limited, 2021)
Selected, peer-reviewed papers from the conference Materials Science and Technology of Additive Manufacturing 2019 (MSTAM), December 10-11, 2019, Bremen, Germany.
Description based upon print version of record.
Keywords: Additive manufacturing -- Congresses.; Materials -- Congresses.; elektronické knihy; electronic books